EVALUATION OF EFFICIENCY OF HEAT EXCHANGING DEVICES BUILT INTO THE THERMAL CYCLIC MACHINES - Bashta, Oleksandr; Nosko, Pavlo; Boyko, Grygory; Tsybrii, Yurii (Problems of Friction and Wear, 2019)
The focus of this work is a method of exergy-economizing calculation for the recuperative and regenerative heat-exchangers that are built-in the thermal cyclic machines. The method is intended for the analysis of efficiency of a prospective design and material for the heat-exchanger that is incorporated into the closed thermodynamic cycle of thermal machines at the initial stage of designing.